SOCIO-ECONOMIC CARRYING CAPACITY ASSESSMENT FOR BUKIT TINGGI - Mohamad, Diana; Jaafar, Mastura; Ismail, Mohd Muzzammil (PLANNING MALAYSIA, 2020)
This paper discusses an assessment of social and economic carrying capacity (CC) in Bukit Tinggi. Bukit Tinggi is a new and emerging highland tourism destination located in Malaysia, thus assessing the present CC level is imperative to ascertain the sustainability of destination competitiveness. The economics of socio CC has been a growing area. The fundamental concept of CC revolves around the analysis of behavioural dynamics, succession, and establishing a dynamic balance of natural ecosystems. This paper, hence, looked into the present socio-economic CC level in Bukit Tinggi in order to understand the extent of tourism developments enabled in Bukit Tinggi without affecting tourists’ tourism experience. The CC data on social (tourist arrival, safety and well-being, place identity, tourism experience) and economic (employment demand/supply, business growth/supply demand, tourism income) aspects were gathered from visitors via self-administered questionnaire survey approach. The findings revealed that more efforts and immediate attention should be given to the socioeconomic CC in Bukit Tinggi mainly because all the studied variables displayed moderate CC level values.